PENGARUH TERAPI BERMAIN POP- UP BOOK TERHADAP KECEMASAN PREOPERATIF MENGGUNAKAN ANESTESI UMUM PADA ANAK USIA SEKOLAH DI RS PKU MUHAMMADIYAH YOGYAKARTA - Nia Handayani; Atik Badi’ah; Budhy Ermawan (Caring : Jurnal Keperawatan, 2017)
A play therapy will release the child from a variety of unpleasant feelings, such as anger, fear, anxiety, and pain. In the United States,> 4 million children undergo surgery each year and it is estimated that 50% - 75% of these show fear and anxiety before surgery (Kain & Alison, 2005). The state of anxious child in the face of surgery will. Research aim to know the influence of pop up book media play therapy on preoperative anxiety level using general anesthesia in school-aged children in PKU Muhammadiyah Hospital Yogyakarta. Method use pre experimental type of study with one group pre test and post test without using control group. Sampling technique with purposive sampling as many as 20 patients of school-age children pre operative with general anesthesia. Data collected was then analysed using Wilcoxon Rank Test. The result pre-test therapy showed moderate anxiety as many as 13 people (65%), post-test play therapy showed moderate anxiety as much as 10 people (50%), decreased in severe anxiety and an increase in mild anxiety by 9 people (45% . Wilcoxon Rank Test test results known level of significance ? = 0,000 (? <0.05). The conclusion there is an influence of pop up book media play therapy on preoperative anxiety level using general anesthesia to school-aged children in PKU Muhammadiyah Hospital Yogyakarta.